If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2n + -7) + -3 = 36 Reorder the terms: 3(-7 + 2n) + -3 = 36 (-7 * 3 + 2n * 3) + -3 = 36 (-21 + 6n) + -3 = 36 Reorder the terms: -21 + -3 + 6n = 36 Combine like terms: -21 + -3 = -24 -24 + 6n = 36 Solving -24 + 6n = 36 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '24' to each side of the equation. -24 + 24 + 6n = 36 + 24 Combine like terms: -24 + 24 = 0 0 + 6n = 36 + 24 6n = 36 + 24 Combine like terms: 36 + 24 = 60 6n = 60 Divide each side by '6'. n = 10 Simplifying n = 10
| 2+10=20 | | f=(1.8x-10)+32 | | -7x=4 | | 7c-d=20 | | 3(2x+3)=4(x-2) | | 3(2x+3)=4 | | 3x-5=5x+11 | | r^2+4r-7=0 | | 15=2x(x-1.5) | | 6(x+1)-7=5(x+8) | | 14x+18=11x-17 | | -(4y+1)-(-3y-3)=-5 | | 11j+8.8=13.2 | | 5a+b=14 | | 7-729+-12+(-3)= | | 9d-3d=18 | | -9=-2-p | | 3x-4=2(3x+5) | | 12(3x-4)=3(12x+7) | | 7-729+-6(-2)+(-3)= | | 22=3x+6x | | 8x-4x+9=30-3x | | 3.5q-2.8-5.6q=-3.1q-2.1 | | -[x-(4x+2)]=2+(2x+7) | | 3q-7=2q | | 26=60-.5x | | 7-9*9*9= | | 25500*n=.17 | | 9x-(4x-12)=42 | | 5x^2+6y^2+2x+5y+13=0 | | 30l+240=50l+160 | | -2*2*2= |